PENGARUH MODAL KEUANGAN TERHADAP KINERJA PERUSAHAAN UKM MELALUI STRATEGI INOVASI (Studi Empiris Perusahaan UKM di Kota Makassar) - Wihalminus Sombolayuk; Indrianty Sudirman; Ria Mardiana Yusuf (Faculty of Economic and Business Universitas STIKUBANK, 2019)
This study aims to explain the effect of financial capital on the performance of SME companies through innovation strategies. In this case, the direct effect of financial capital on innovation strategies is explained, the direct effect of financial capital on SME company performance and, the effect of financial capital on the performance of SME companies through innovation strategies. This research is a quantitative study with an analysis unit of SME companies in Makassar City. the number of samples of 180 SME companies taken accidentally. The analytical methods that are used include validity, reliability, goodness of fit, conventional factor analysis, regression analysis, and path analysis with the help of Amos software. The results of this study indicate that: a) financial capital does not have a direct positive effect on innovation strategy b) Wear capital has a significant positive direct effect on SME company performance c) Innovation strategy does not have a significant effect in mediating between capital gains and SME company performance. Keywords: Financial Capital, Innovation Strategy and SME Company Performance.